2021
DOI: 10.1016/j.molmet.2021.101357
|View full text |Cite
|
Sign up to set email alerts
|

Dpp4+ interstitial progenitor cells contribute to basal and high fat diet-induced adipogenesis

Abstract: Objective The capacity to generate new adipocytes from precursor cells is critical for maintaining metabolic health. Adipocyte precursor cells (APCs) constitute a heterogenous collection of cell types; however, the contribution of these various cell types to adipose tissue expansion in vivo remains unknown. The aim of the current study is to investigate the contribution of Dpp4+ progenitors to de novo adipogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…In mice, DPP4 + interstitial progenitor cells can form adipocytes in all depots but are induced to make adipocytes only in gonadal AT with obesity. 17 We used immunofluorescence (IF) microscopy with the IM-ASC specific marker TM4SF1 (transmembrane 4 L six family member 1), a surface tetraspanin to identify the location of IM-ASC. TM4SF1 + CD31 -IM-ASC were identified in the perivascular niche, distinct from TM4SF1 + CD31 + EC (Figure 3G).…”
Section: Depot Specific Differences In Adipose Stromal Cells (Asc)mentioning
confidence: 99%
See 2 more Smart Citations
“…In mice, DPP4 + interstitial progenitor cells can form adipocytes in all depots but are induced to make adipocytes only in gonadal AT with obesity. 17 We used immunofluorescence (IF) microscopy with the IM-ASC specific marker TM4SF1 (transmembrane 4 L six family member 1), a surface tetraspanin to identify the location of IM-ASC. TM4SF1 + CD31 -IM-ASC were identified in the perivascular niche, distinct from TM4SF1 + CD31 + EC (Figure 3G).…”
Section: Depot Specific Differences In Adipose Stromal Cells (Asc)mentioning
confidence: 99%
“…We now know that this approach lacks rigor, as scRNAseq data from mice and humans demonstrate substantial heterogeneity in ASC and adipocytes. 5,6,16,17 Our goal was to apply snRNAseq analysis to banked frozen AT and describe the complete transcriptome of human VAT and SAT. We studied VAT and SAT samples from a cohort of lean human subjects and subjects with obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, knowing the potential of APCs to undergo differentiation into myo broblasts when exposed to an in ammatory or brotic environment, it is tempting to speculate that the CD54 subpopulation will display a pro-brogenic/pro-in ammatory phenotype in the pathological model. Accumulation of CD54 + APCs in subcutaneous adipose tissue of high-fat-diet-induced obese mice without a corresponding increase in mature adipocyte differentiation support this hypothesis 15 . The role of CD142 APCs in adipogenesis is more controversial because this subpopulation is described as fully adipogenic or as inhibitor of adipogenic differentiation via paracrine effects 16 .…”
mentioning
confidence: 81%
“…However, PDGFRα + CD9 low cells almost completely disappeared with AT fibrosis upon HFD feeding ( 33 ). Recently, a highly proliferative dipeptidyl peptidase-4 (DPP4) + APC population was identified that gives rise to highly adipogenic ICAM1 + preadipocytes as well as a CD142 + adipogenic cell population, which was further studied by DPP4-Cre mediated lineage tracing experiments ( Figure 1 ) ( 26 , 34 ). Moreover, various other cell surface molecules have been described to distinguish APC and preadipocyte populations and we recently showed that the amino acid transporter ASC-1 regulates the commitment of APCs to become either white or beige adipocytes ( 35 , 36 ).…”
Section: Heterogeneity and Hierarchy In Adipose Progenitor Cellsmentioning
confidence: 99%